Respuesta :

[tex](\stackrel{x_1}{2}~,~\stackrel{y_1}{8})\qquad (\stackrel{x_2}{5}~,~\stackrel{y_2}{-4}) ~\hfill \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{-4}-\stackrel{y1}{8}}}{\underset{run} {\underset{x_2}{5}-\underset{x_1}{2}}}\implies \cfrac{-12}{3}\implies -4 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{8}=\stackrel{m}{-4}(x-\stackrel{x_1}{2}) \\\\\\ y-8= -4x+8\implies y=-4x+16[/tex]